Case report on management of frontal sinus fracture using foley catheter balloon inflation - Ahmed ElMinshawi; Joshua Cheng; Patrick J. McCann (Elsevier, 2022)
The frontal sinus fracture management is complicated due to its anatomical location. Several classifications have been made to facilitate the methods of treatment which varies from simple conservative observation to complex surgical intervention.The main goal is to achieve "safe functional sinus" either conservatively or surgically. Many surgical approaches have been employed to access the sinus, however, less invasive techniques are currently being utilized.Previously, endoscopic reduction by inflating a balloon catheter was used to tread displaced orbital floor and frontal sinus through their ostia in the nasal cavity, however, no fixation was mentioned after maintaining reduction.This case report will briefly describe frontal sinus reduction using balloon inflation and fixation via titanium microplates through an existing laceration.